A genome-wide association study of the human metabolome in a community-based cohort - Rhee, Eugene P; Ho, Jennifer E; Chen, Ming-Huei; Shen, Dongxiao; Cheng, Susan; Larson, Martin G; Ghorbani, Anahita; Shi, Xu; Helenius, Iiro T; O'Donnell, Christopher J; Souza, Amanda L; Deik, Amy; et al. (Cell metabolism, 2013)
Because metabolites are hypothesized to play key roles as markers and effectors of cardiometabolic diseases, recent studies have sought to annotate the genetic determinants of circulating metabolite levels. We report a genome-wide association study (GWAS) of 217 plasma metabolites, including >100 not measured in prior GWAS, in 2076 participants of the Framingham Heart Study (FHS). For the majority of analytes, we find that estimated heritability explains >20% of interindividual variation, and that variation attributable to heritable factors is greater than that attributable to clinical factors. Further, we identify 31 genetic loci associated with plasma metabolites, including 23 that have not previously been reported. Importantly, we include GWAS results for all surveyed metabolites and demonstrate how this information highlights a role for AGXT2 in cholesterol ester and triacylglycerol metabolism. Thus, our study outlines the relative contributions of inherited and clinical factors on the plasma metabolome and provides a resource for metabolism research.